Novel technology at hand to measure skin hydration by Biodisplay smartphone touch screen panel - YoungHwan Choi (Scientific Reports, 2021)
Abstract Skin hydration is generally evaluated using devices that measure capacitance or conductance. A new technology (Biodisplay) was developed to provide accurate measurements of skin hydration at the contact site. This study aimed to test the reliability of the Biodisplay by comparing its performance results with those of similar devices currently used to objectively assess skin hydration. For each of the 30 participants, skin hydration was measured at each of the defined points on the forearm three times using the Biodisplay and a Hydration probe (HP), an objective measurement device of skin hydration. We also evaluated skin hydration of the arm using both tools after applying moisturizers to evaluate interferences from skin care products. The reliability and reproducibility of each device were analyzed by intraclass correlation coefficients (ICC), and the correlation of the two devices was evaluated by Pearson’s correlation coefficients (PCC). The Biodisplay demonstrated moderate-to-excellent reliability (ICC: (0.741–0.980)), but lower reliability than the HP (ICC: (0.953–0.980)). The skin hydration measurements made by the two devices were demonstrated to be significantly correlated, showing moderate correlations (PCC: 0.601). The Biodisplay can provide reasonably reliable and accurate measurements for skin hydration with the strong points of portability and accessibility.